2010
DOI: 10.1002/humu.21265
|View full text |Cite
|
Sign up to set email alerts
|

An interactive web-tool for molecular analyses links naturally occurring mutation data with three-dimensional structures of the rhodopsin-like glycoprotein hormone receptors

Abstract: ABSTRACT:The collection, description and molecular analysis of naturally occurring (pathogenic) mutations are important for understanding the functional mechanisms and malfunctions of biological units such as proteins. Numerous databases collate a huge amount of functional data or descriptions of mutations, but tools to analyse the molecular effects of genetic variations are as yet poorly provided. The goal of this work was therefore to develop a translational web-application that facilitates the interactive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Most activating GPHR mutations were found in the 7TM domain (46). Based on previous studies (5), we can rule out that the constitutive activity of those 7TM mutations is p10 sequence-mediated.…”
Section: Figure 7 P10 Activates Gphrs In Tissuesmentioning
confidence: 73%
“…Most activating GPHR mutations were found in the 7TM domain (46). Based on previous studies (5), we can rule out that the constitutive activity of those 7TM mutations is p10 sequence-mediated.…”
Section: Figure 7 P10 Activates Gphrs In Tissuesmentioning
confidence: 73%
“…This novel feature can be used to identify interacting residues as counterparts and to evaluate potential mechanisms of molecular malfunction caused by specific mutations. We recently described the interactive 3D-Search applet in detail, demonstrating its usefulness in the analysis of naturally occurring mutations (17).…”
Section: An Innovative New Tool: the Interactive Structure-based Searchmentioning
confidence: 99%
“…This provides a platform for investigation of molecular mechanisms and a better understanding of protein malfunctions. Recently, we described one of the extensions in detail, namely applications for the analysis of pathogenic mutations in three-dimensional (3D) structures (17). Here, we will focus on the complete renewal of the previous database version which includes the addition of several new features as extensions.…”
mentioning
confidence: 99%
“…The high conservation of these amino acids in contrast to other hydrophobic residues in this region, like Leu 265 , Leu 267 , or Leu 270 , indicates their evolutionary importance for the TSHR. Screening of available mutagenesis data for the LRRDs of the GPHRs (see the SSFA-GPHR database on the World Wide Web) (57,58) revealed that mutations at specific hydrophobic key positions of the typical LRR profile always lead to an impaired receptor expression level. The hydrophobic positions that were identified here as fold-sensitive match exactly this repeat pattern of hydrophobic residues by pointing into the interior of the LRR domain model (Fig.…”
Section: Hydrophobic Amino Acids At the Junction Between The Leucine-mentioning
confidence: 99%